"Don't Let God Step In Human Waste": Interpretation Of Deuteronomy 23:14–15 In The Context Of Cholera In Zambia. (December 2021) - Kangwa, Jonathan
Climate change and health challenges such as the HIV and AIDS have motivated religious leaders to rethink their beliefs and practices, considering how to apply these to health crises. Christian theologians and biblical scholars have risen to the occasion and developed new ways of interpreting the bible that offer a response to current situations. The new ways of interpreting the bible include approaching the text with a degree of wariness and traditional readings of the bible are often transgressed. The experience of the marginalised or the dismembered is used as a starting point for bible interpretation and theological reflection. This paper contributes to the shifts in bible interpretation and theological reflection by offering an eco-theological interpretation of Deuteronomy 23:14–15 in the context of cholera. The paper shows that, in the context of cholera in Zambia, an eco-theological interpretation of the biblical text can foster hygiene and proper management of human waste which would be an important contribution to the prevention of cholera outbreaks.